2013
DOI: 10.1590/s1413-35552012005000068
|View full text |Cite
|
Sign up to set email alerts
|

Profile and scientific output analysis of physical therapy researchers with research productivity fellowship from the Brazilian National Council for Scientific and Technological Development

Abstract: | Objective: To describe the profile and the scientific output of physical therapists researchers holding a research productivity fellowship (PQ) from the Brazilian National Council of Scientific and Technological Development (Conselho Nacional de Desenvolvimento Científico e Tecnológico-CNPq). Method: This is a cross-sectional study, which has evaluated the Lattes Curriculum of all PQ physiotherapy researchers registered at CNPq holding a research productivity fellowship in the period of 2010. The variables a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 18 publications
2
20
0
3
Order By: Relevance
“…In one study in which the impact indicators were compared of two randomly selected populations of Physiotherapy and Comparative Biochemistry researchers, having one group coming from Latin America and the other from developed countries 28 . These numbers were similar to the ones found in the medical areas as well as in the study involving PQ in Public Health 11 -which covers professional in the medical areaand way above the index found in the study with Physiotherapy grant holders 20 (on Scopus database, the average observed was of 5.3; when evaluated on Web of Science database, average 3.0 was found). However, H-index has some limitation to favor the researchers with long careers, as well as the ones who work in areas with high frequency of quotes 29 .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In one study in which the impact indicators were compared of two randomly selected populations of Physiotherapy and Comparative Biochemistry researchers, having one group coming from Latin America and the other from developed countries 28 . These numbers were similar to the ones found in the medical areas as well as in the study involving PQ in Public Health 11 -which covers professional in the medical areaand way above the index found in the study with Physiotherapy grant holders 20 (on Scopus database, the average observed was of 5.3; when evaluated on Web of Science database, average 3.0 was found). However, H-index has some limitation to favor the researchers with long careers, as well as the ones who work in areas with high frequency of quotes 29 .…”
Section: Discussionsupporting
confidence: 86%
“…Analyzing the researchers' profile, we noticed the predominance of male gender involving other areas, such as Chemistry9and Dentistry 18 . However, this fact has been changing in the last years, in areas such as Nursing 1 and Physiotherapy 20 , in which we observe the predominance of the female gender among the grant holders of PQ/CNPq, alongside with the history of feminization of jobs. It is important to mention the same tendency observed in two studies involving PQ in the field of Public Health: in the first study 155 resumes Lattes of researchers were analyzed in the three years of 2004-2006, we could observe the similarity between the male and female gender (1.03:1) 11 .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…É importante destacar que este aumento também foi encontrado nos estudos que avaliam outra área 16 . O estudo aponta um aumento das publicações em perió dicos indexados, tanto nacionais quanto internacionais.…”
Section: Introductionunclassified